Determinants of circular migration patterns to Badung regency - Pebrian, I Kadek Rio Dwi; Mustika, Made Dwi Setyadhi (Universitas Ahmad Dahlan, 2024)
The influence of migration causes the growth of the population in a region. Migration occurs due to imbalances in development, especially in the economic sector. Whereby people migrate to obtain employment due to high wages and job opportunities in the destination area. This research analyzes the factors influencing the population's decision to engage in circular migration to Badung Regency. The analytical tool used is logistic regression analysis, specifically Binary Logistic Regression. The sample consists of 123 respondents. The research results indicate that variables such as wage levels, number of family dependents, gender, activities in the area of origin, distance, age, and squared age collectively and significantly influence the decision of the population to engage in circular migration to Badung Regency. Partially, the research results show that the number of family dependents, gender, activities in the area of origin, and age significantly positively affect the decision of the population to engage in circular migration to Badung Regency. Meanwhile, wage levels, distance, and squared age significantly negatively affect the population's decision to engage in circular migration to Badung Regency.